Estimated radiation dose and image quality comparison of the scan protocols in dual‐source computed tomography coronary angiography. Issue 4 (21st January 2013) - Karaarslan, Ercan; Ulus, Sıla; Bavbek, Cengiz
Abstract Introduction Radiation exposure from computed tomography coronary angiography (CTCA) is of particular concern and several techniques have been introduced to lower the radiation dose. In this study, we aimed to compare the diagnostic image quality and estimated radiation dose of the three CTCA acquisition protocols in a recently introduced second generation dual‐source computed tomography. Methods Two hundred consecutive subjects underwent dual‐source CTCA by using high‐pitch spiral, sequential and retrospective spiral protocols. Effective radiation dose, expressed in millisieverts, was calculated as the product of the dose‐length product times a conversion factor of 0.014. Image quality was evaluated on a per‐segment basis, with a four‐point scale. Results For the high‐pitch spiral, sequential and retrospective spiral protocols, mean effective radiation doses were 1.41 ± 0.56, 5.50 ± 2.06 and 7.79 ± 2.25 mSv and mean per‐subject image scores were 2.8 ± 0.7, 2.2 ± 0.8 and 2.5 ± 0.8, respectively. Radiation dose of the high‐pitch mode was significantly lower (P < 0.001) than the sequential and retrospective spiral modes, and statistical analysis for image quality revealed a significant difference between the high‐pitch spiral and the sequential modes (P < 0.05). Conclusion Dual‐source CTCA using high‐pitch acquisition considerably lowers radiation exposure in subjects with a low and stable heart rate and maintains good image quality, especially when the subjects have a body mass index ≤25 and a tube voltage of 80 or 100 kV is used. However, when sequential and retrospective spiral modes are used in the same device, mean radiation doses can increase roughly three and five times more, respectively.